Business cycles in the construction industry: identification,analysis, evaluation - Mogolivets, А. (Ways to Improve Construction Efficiency, 2019)
A theoretical generalization of approaches to economic cyclicality, the various types of economic cycles, their features and reasons are analyzed. Based on the indicators of changes in the volume of GDP of Ukraine and construction in 2002-2018, it is determined that economic cyclicality is inherent in the Ukrainian economy, among the fluctuations of business activity, it is quite clearly possible to identify two-four-year cycles of Kitchin, cycles of Zhyuglyar, which have a period of fluctuations of seven to eleven years.